Local Diagnostic Reference Levels for Paediatric Head CT Procedures - Gricienė, Birutė; Šiukšterytė, Monika (Acta medica Lituanica, 2021)
Background. Patients, especially children, are exposed to substantially high doses of ionising radiation during computed tomography (CT) procedures. Children are several times more susceptible to ionising radiation than adults. Diagnostic reference levels (DRLs) are an important tool for monitoring and optimising patient radiation exposure from radiological procedures. The aim of this study is to estimate the ionising radiation exposure doses and set local DRLs for head CT examinations according to age and to compare local DRLs with national and European DRLs and with literature data in other countries. Materials and methods. Scan parameters of single-phase head CT examinations were collected. Patients were grouped by age in the following intervals: <1, 1−5, 5−10, 10−15 and 15−18 years. Local age-based DRLs set as the 3rd quartile of the median dose-length product (DLP) were calculated. Literature analysis was performed on PubMed search engine on inclusion criteria: publication date 2015–2020, used keywords paediatric computed tomography, paediatric CT, diagnostic reference levels (DRLs). The 23 articles discussing paediatric DRLs were further analysed. Results. Data was collected from 194 paediatric head CT examinations performed in 2019. The median DLP values for head CT were 144.3, 233.7, 246.4, 288.9, 315.5 for <1, 1−5, 5−10, 10−15 and 15−18 years old groups. Estimated local DRLs for head CT examinations are 170, 300, 310, 320, 360 mGy*cm for <1, 1−5, 5−10, 10−15 and 15−18 years age groups respectively and 130, 210, 275, 320 mGy*cm for 0−3 months, 3 months−1 year, 1−6 years and ≥ 6 years age groups respectively. Conclusions. Results of this study showed that settled new local DRLs of head CT examinations were 2–4 times lower than national DRLs and about 2 times lower than European DRLs. Moreover, the study indicated that paediatric head CT doses are significantly lower in comparison with those indicated in the majority of published data from other hospitals over the last 6 years. Patient dose assessment and local DRLs establishment plays important role in future exposure optimisation.